PENGARUH KEPEMIMPINAN YANG MELAYANI DAN IKLIM ORGANISASI PADA KETERIKATAN KERJADENGAN KEPUASAN KERJA SEBAGAI VARIABEL PEMEDIASI (STUDI PADA DOSEN STIE APRIN PALEMBANG) - Cindy Shafira Ulfa (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
In private universities, the amount of competitors that are plenty has forced them to keep improving their quality and the welfare of the lecturers as teaching staff. The servant leadership and the organizational climate are important things to consider, remembering that both are some of the factors which influence job satisfaction and work engagement. This research aims to determine the effect of servant leadership and organizational climate on work engagement; as well as to determine the effect of job satisfaction as a mediator variable. The sampling method used is census technique. The primary data collection method was done using a questionnaire of 44 respondents. The analytical tool used is SEM (Structural Equation Model) with SmartPLS version 3.0. The result of the research shows that servant leadership affects work engagement, organizational climate affects work engagement, and job satisfaction as the mediator of servant leadership and organizational climate on work engagement has a partial effect.